A COMPARATIVE STUDY OF INDUCTIVE VS. DEDUCTIVE APPROACHES IN TEACHING GRAMMAR (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The teaching of grammar has long been a central component of English language instruction, and choosing the most effective method remains a topic of pedagogical interest. This study aims to compare the inductive and deductive approaches in teaching English grammar to EFL (English as a Foreign Language) learners. The inductive method involves guiding students to discover grammatical rules through examples and language use, while the deductive method presents rules first, followed by practice. The research draws on classroom observations, student performance data, and teacher interviews conducted in secondary and tertiary educational contexts. Findings suggest that the inductive approach enhances learner engagement and long-term retention, particularly among intermediate-level students, whereas the deductive approach proves more efficient for introducing complex rules in a time-limited setting. The study concludes that a balanced, learner-centered approach tailored to proficiency level and learning objectives may yield the best results in grammar instruction.